2020
DOI: 10.1161/circulationaha.120.045769
|View full text |Cite
|
Sign up to set email alerts
|

Factor Xa Inhibitor-Related Intracranial Hemorrhage

Abstract: Background: Since the approval of the oral factor Xa inhibitors, there have been concerns regarding the ability to neutralize their anticoagulant effects after intracranial hemorrhage (ICH). Multiple guidelines suggest using prothrombin complex concentrates (PCCs) in these patients on the basis of research that includes a limited number of patients with ICH. Given this, we aimed to evaluate the safety and efficacy of PCCs for factor Xa inhibitor–related ICH in a large, multicenter cohort of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 26 publications
1
36
0
1
Order By: Relevance
“…Therapeutic strategies have included supportive care, antifibrinolytic agents (aminocaproic acid, tranexamic acid), and coagulation factor therapies (prothrombin complex concentrates, plasma, factor VIII inhibitor bypassing activity). Recent reports have described the use of these agents in patients with ICrH, 25 , 26 , 32 , 33 although the mechanistic basis for their effectiveness is controversial. 34 Furthermore, their efficacy may be restricted in the presence of higher anti-FXa levels, 35 and the reports provide limited or no information regarding baseline anti-FXa activity.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic strategies have included supportive care, antifibrinolytic agents (aminocaproic acid, tranexamic acid), and coagulation factor therapies (prothrombin complex concentrates, plasma, factor VIII inhibitor bypassing activity). Recent reports have described the use of these agents in patients with ICrH, 25 , 26 , 32 , 33 although the mechanistic basis for their effectiveness is controversial. 34 Furthermore, their efficacy may be restricted in the presence of higher anti-FXa levels, 35 and the reports provide limited or no information regarding baseline anti-FXa activity.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we observed higher risk profiles in terms of age and comorbidities in patients taking FXa inhibitors than spontaneous ICH without preceding use of OAC. Despite no significant differences in the likelihood of discharge home and functional status at discharge, FXa 17,18 Comparing the impact of various reversal strategies can be difficult because of selection bias and concomitant medication use in ICH, making it hard to disentangle the effectiveness of various treatments. 19 Furthermore, because anticoagulant levels are rarely captured, further research is required to measure clinical outcomes in the context of anticoagulant levels in addition to bleeding size and severity.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that non-vitamin K OACs may be a better choice than warfarin when combination strategy is warranted.Unlike warfarin-related ICH, the best management strategy for FXa inhibitor-associated ICH remains uncertain. The 2019 European Stroke Organisation Guidelines17,18 recommend andexanet-α in ICH with rivaroxaban or apixaban or prothrombin complex concentrate to normalize coagulation tests if specific reversal agents are not available. However, the quality of evidence is low because of a lack of randomized clinical trials and uncertainty regarding the benefit and harm of the reversal treatment.…”
mentioning
confidence: 99%
“…14 4F-PCC contains nonactivated coagulation factors II, VII, IX, and X competing with the effects of FXa inhibitors, increasing thrombin generation, and facilitating clot formation. 14,15 With the exception of Panos et al 16 clinical evaluations of 4F-PCC for reversal of FXa inhibitors are limited to small cohort studies, collectively estimating hemostatic efficacy rates from 60% to 94.7%. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] A meta-analysis of 10 studies evaluating 4F-PCC for FXa-inhibitor reversal found a pooled thrombotic event rate of 4% and a mortality rate of 16%.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 With the exception of Panos et al 16 clinical evaluations of 4F-PCC for reversal of FXa inhibitors are limited to small cohort studies, collectively estimating hemostatic efficacy rates from 60% to 94.7%. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] A meta-analysis of 10 studies evaluating 4F-PCC for FXa-inhibitor reversal found a pooled thrombotic event rate of 4% and a mortality rate of 16%. 22 Based on the available literature the American Society of Hematology has suggested the use of either 4F-PCC or andexanet alfa for patients with FXa-inhibitor-associated bleeding.…”
Section: Introductionmentioning
confidence: 99%